Biosynthesis of orchid-like volatile methyl jasmonate in tea (Camellia sinensis) leaves in response to multiple stresses during the shaking process of oolong tea. (May 2021) - Feng, Yingying; Wang, Jingming; Zhao, Yifan; Zhang, Mengting; Zhou, Zixiang; Li, Yating; Hu, Yunqing; Wu, Yi; Feng, Zhihui; Schwab, Wilfried; Wan, Xiaochun; Song, Chuankui
Abstract: Methyl jasmonate (MeJA), a significant fatty acid derivative, contributes to the main floral aroma of oolong tea. However, in tea plants, the mechanism of MeJA biosynthesis and the enzymes that participate in its formation is still unclear. In this study, the full length of the first jasmonic acid carboxyl methyltransferase ( JMT ) gene from Camellia sinensis was amplified and the biochemical function of the recombinant C. sinensis JMT (CsJMT) protein was studied after coexpression in Escherichia coli . The recombinant CsJMT protein could transfer the methyl groups to jasmonic acid to produce orchid-like volatile 1R, 2R-MeJA in vitro . Volatile 1R, 2R-MeJA was detected by gas chromatography–mass spectrometry during the shaking process of oolong tea, and the accumulation of 1R, 2R-MeJA was found to correlate with CsJMT expression. Further investigation showed that the mechanical injury and low-temperature stress could significantly induce CsJMT expression and MeJA accumulation after harvest. These results demonstrated that CsJMT catalyzed the production of MeJA in tea plants and provided a basis for studying the formation and accumulation of orchid-like volatile MeJA during the shaking process of oolong tea. Graphical abstract: Image 1 Highlights: The dynamic change in methyl jasmonate (MeJA) content during the shaking process of oolong tea was studied. The first jasmonic acid carboxyl methyltransferase ( CsJMT ) in tea plants was discovered. CsJMT was involved in the formation of MeJA after harvest (the shaking process of oolong tea). Mechanical injury and low temperature synergistically promoted the accumulation of MeJA.